2020
DOI: 10.3390/ani10040624
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed MicroRNAs and Their Potential Target Genes in Adipose Tissue from Pigs with Highly Divergent Backfat Thickness

Abstract: Fatty traits are very important in pig production. However, the role of microRNAs (miRNAs) in fat deposition is not clearly understood. In this study, we compared adipose miRNAs from three full-sibling pairs of female Landrace pigs, with high and low backfat thickness, to investigate the associated regulatory network. We obtained an average of 17.29 million raw reads from six libraries, 62.27% of which mapped to the pig reference genome. A total of 318 pig miRNAs were detected among the samples. Among them, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Our previous report showed that miR-125 could impair the composition of porcine intramuscular fat [36]. Moreover, a study indicated that SSC-miR-141 [37], which is downregulated in high backfat tissues that target FASN, might inhibit fatty acid synthesis in pig backfat tissues. Here, we showed that miR-370-3p inhibited 3T3-L1 cell adipogenesis and changed the fatty acid composition in mature adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous report showed that miR-125 could impair the composition of porcine intramuscular fat [36]. Moreover, a study indicated that SSC-miR-141 [37], which is downregulated in high backfat tissues that target FASN, might inhibit fatty acid synthesis in pig backfat tissues. Here, we showed that miR-370-3p inhibited 3T3-L1 cell adipogenesis and changed the fatty acid composition in mature adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…SREBF-1 ( SREBP-1c ) gene: Sterol regulatory element-binding transcription factor-1c ( SREBF-1c ) was suggested to be an important lipogenic gene that has a critical role in the gene transcription mechanism and regulation of muscle fat deposition [ 62 , 102 ]. The role of SREBF-1 in fat metabolism and IMF accretion remains contradictory between studies and could be breed dependent.…”
Section: Genes Involved In Fat Metabolism and Imf Accretion In Pigsmentioning
confidence: 99%
“…Today, about 778 QTLs related to different traits have been identified and documented in the pig QTL database, pigQTLdb (see , accessed on 23 December 2021). Studies by Harper and Pethick [ 102 ] reported that the onset of marbling is located at chromosomal regions for QTL on chromosome 5 (SSC5), which is responsible for muscle growth and fat deposition. This QTL was genetically related to the RARγ gene which is involved in the transcription and expression of many other genes [ 114 ].…”
Section: Qtl Regions and Snps For Fat Metabolism And Imf Accretion In Pigsmentioning
confidence: 99%
“…The over-expression of miR-143 could accumulate more triglycerides in the adipocytes and therefore promote adipogenesis [ 28 ]. Three miRNA, miR-137, miR-144, and miR-122-5p, were defined as the candidate key regulators of fat deposition [ 31 ].…”
Section: The Mirnas Functions In Feed Efficiencymentioning
confidence: 99%